Fenomena Acquired Hemofilia A (AHA) Setelah Infeksi Covid-19: Sebuah Tinjauan Literatur - Niluh Ayu Sri Saraswati (Utan Kayu Publishing, 2021)
Acquired hemophilia A (AHA) is a rare autoimmune disease caused by circulating autoantibodies directed against the clotting factor VIII (FVIII) that leads to bleeding. It is often associated with pregnancy, autoimmune, malignancy, drugs, or infection – including COVID-19. Recently, there are 2 reported cases of AHA following COVID-19 infections. This study aims to examine the results of various studies from several journals about the association between COVID-19 infection and AHA. Those studies were collected and reviewed then written as a literature review study. As AHA is included into coagulation disorders, which also known as coagulopathy, is associated with thrombotic complications, and is well described as one of the COVID-19 complications. So, it is possible that COVID-19 infection leading to AHA due to its thrombotic complications. Moreover, COVID-19 infection is causing immune dysregulation, rising the FVIII autoantibodies which also contributes to caused AHA. So, it is important for the clinician to know that COVID-19 infections could trigger the emerging of AHA, as it is one of the thrombotic complications in COVID-19 infection. Further study about this phenomenon is needed. ABSTRAK: Acquired hemofilia A (AHA) merupakan sebuah penyakit autoimun langka yang disebabkan oleh antibodi di dalam tubuh yang menyerang faktor VIII (FVIII. AHA seringkali berkaitan dengan kehamilan, autoimun, keganasan, penggunaan obat-obatan, serta infeksi – termasuk COVID-19. Belakangan ini terdapat 2 buah kasus AHA yang dilaporkan terjadi setelah pasien mengalami infeksi COVID-19. Studi ini bertujuan untuk mengamati hasil studi dari berbagai jurnal mengenai hubungan antara infeksi COVID-19 dengan AHA. Studi tersebut dikumpulkan dan ditelaah, kemudian dituangkan kembali dalam bentuk studi review literatur. AHA merupakan kelainan koagulasi yang disebut juga sebagai koagulopati, yang berhubungan dengan komplikasi thrombosis, salah satu manifestasi komplikasi dari infeksi COVID-19. Oleh karena itu, infeksi COVID-19 dapat menginduksi terjadinya AHA sebagai salah satu komplikasi thrombosis yang ditimbulkan. Infeksi COVID-19 juga menimbulkan disregulasi imun yang meningkatkan pembentukan autoantibodi terhadap FVIII sehingga menjadi kontributor terjadinya AHA. Oleh karena itu, perlu diketahui bahwa infeksi COVID-19 dapat mencetuskan terjadinya AHA sebagai salah satu komplikasi thrombosis yang ditimbulkan. Studi lebih lanjut mengenai fenomena tersebut masih diperlukan untuk mengetahui lebih dalam mengenai kaitan antara AHA dengan infeksi COVID-19.